2013
DOI: 10.1124/mol.113.084988
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Platelet-Tumor Cell Cross-Talk Prevents Platelet-Induced Overexpression of Cyclooxygenase-2 in HT29 Human Colon Carcinoma Cells

Abstract: Cyclooxygenase (COX)-2-derived prostanoids can influence several processes that are linked to carcinogenesis. We aimed to address the hypothesis that platelets contribute to aberrant COX-2 expression in HT29 colon carcinoma cells and to reveal the role of platelet-induced COX-2 on the expression of proteins involved in malignancy and marker genes of epithelialmesenchymal transition (EMT). Human platelets cocultured with HT29 cells rapidly adhered to cancer cells and induced COX-2 mRNA expression, but not prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 50 publications
4
138
0
4
Order By: Relevance
“…Several studies have suggested mechanisms underlying the antitumor effects of aspirin, such as prevention of COX-2 overexpression in tumor cells due to inflammation in the absence of platelets or to direct platelet-tumor cell interaction [10,19] or prevention of this interaction by inhibiting cyclooxygenase-1 (COX-1) in platelets [12]. Although COX-1 is expressed constitutively in various tissues, COX-2 is produced by stimulation such as inflammation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested mechanisms underlying the antitumor effects of aspirin, such as prevention of COX-2 overexpression in tumor cells due to inflammation in the absence of platelets or to direct platelet-tumor cell interaction [10,19] or prevention of this interaction by inhibiting cyclooxygenase-1 (COX-1) in platelets [12]. Although COX-1 is expressed constitutively in various tissues, COX-2 is produced by stimulation such as inflammation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dovizio et al showed that the induction of COX-2 overexpression by platelet-tumor cell cross-talk could be inhibited by disrupting galectin-3 function or collagen receptor-mediated platelet adhesion. Their study suggested that blocking physical interactions by targeting collagen binding sites could be an alternate means of affecting COX-2 [529]. …”
Section: Nsaids and Coxibs Inhibit Cancermentioning
confidence: 99%
“…Another mechanism could involve the cleavage of galectin-3 by SspB (as shown here) and by neutrophil-released metalloproteases and serine proteases (25,27,28), impairing the production of immunomodulatory ROS, as well as galectin-3-dependent opsonophagocytic processes, possibly resulting in impaired infection control and aggravated tissue destruction (14,15,24). Furthermore, protease-cleaved galectin-3 (CRD) may possibly have proinflammatory effects per se, contributing to inflammatory tissue damage, as seen in other disease models (51)(52)(53)(54). These suggested mechanisms can appear to work in opposite directions, but opposing functions are well-known phenomena in the galectin field.…”
Section: Discussionmentioning
confidence: 99%